Analysis of The Influence of Revenue, Expense, and Liquidity on Financial Performance (Literature Review) - Unggul Uji Nurhayati; Hapzi Ali (Dinasti International Journal of Management Science, 2023)
Article Literature Review Analysis of the Effect of Revenue, Expense and Liquidity on Financial Performance is a scientific article that aims to build a research hypothesis on the influence of variables to be used in further research, within the scope of the science of Financial Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar, Mendeley and other academic online media. The results of this literature review article are: 1) Revenue affects financial performance; 2) Expense has an effect on Financial Performance; and 3) Liquidity affects Financial Performance.